Comparison of conventional methods for bowel length measurement in laparoscopic surgery to a novel computer-assisted 3D measurement system - Wagner, Martin; Mayer, Benjamin; Bodenstedt, Sebastian; Kowalewski, Karl-Friedrich; Nickel, Felix; Speidel, Stefanie; Fischer, Lars; Kenngott, Hannes Götz; Müller, Beat P. (Obesity surgery, 2021)
Accurate laparoscopic bowel length measurement (LBLM), which is used primarily in metabolic surgery, remains a challenge. This study aims to three conventional methods for LBLM, namely using visual judgment (VJ), instrument markings (IM), or premeasured tape (PT) to a novel computer-assisted 3D measurement system (BMS).
Gesehen am 16.02.2023